Inhibitory Effect of Lotus Leaf-Enriched Flavonoid Extract on the Growth of HT-29 Colon Cancer Cells through the Expression of PI3K-Related Molecules - Chong Li (BioMed Research International, 2022)
Objectives. Lotus leaf is rich in flavonoids, and this study is aimed at examining the inhibitory effect of lotus leaf-enriched flavonoid extract (LLEFE) on HT-29 colon cancer cells through phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) expression regulation. Methods. Lotus leaves were extracted by ethanol and purified using FL-3 macroporous resin to create the LLEFE. HT-29 colon cancer cells were tested using various methods: their proliferation was observed by 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-di-phenytetrazoliumromide (MTT) assay, their survival status was observed by fluorescence staining, their oxidative stress level was observed by biochemical kits, and their mRNA expression was determined by quantitative polymerase chain reaction (qPCR) assay. Additionally, the composition of the flavonoids in lotus leaf was determined by HPLC. Results. The results showed that the proliferation of NCM460 normal human colon cells was not affected by 0–500 μg/mL LLEFE but the proliferation of HT-29 human colon cancer cells decreased. LLEFE increased the LDH level in an HT-29 colon cancer cell culture medium; also increased the superoxide dismutase (SOD), catalase (CAT) activities, and glutathione (GSH) level in HT-29 cells; and decreased the malondialdehyde (MDA) level. Further experimental results showed that LLEFE upregulated the expression of SOD1, CAT, and GSH mRNA and downregulated the expression of PI3K, Akt, and mammalian target of rapamycin (mTOR) in HT-29 cells. The high-performance liquid chromatography (HPLC) results showed that kaempferin, hyperoside, astragaloside, phloridzin, and quercetin were the main chemical constituents of lotus leaf. Conclusion. Lotus leaves contain functional flavonoids that inhibit the proliferation of HT-29 colon cancer cells and regulate the expression of PI3K/Akt through five important chemicals.